Prasangka Sosial dan Efektivitas Komunikasi Antarkelompok - Ahmad Sihabudin (MediaTor (Jurnal Komunikasi), 2008)
Baduy community is one of ethnics known as Isoated Custom Comunity (Komunitas Adat Terpencil). The research is a quantitative research, using survey methode. The data was colected from sample of population. The esearch is aimed to describe the correlation and effect among variables by hypotesis test, called as explanatory research. The result shows that social distance in Baduy Dalam Community deeply determines the effectivity of Ciboleger communication. It means, the farther social distance in Baduy Community is the less effective Ciboleger communication is. Discriminations in Baduy Dalam Community does not determine the  ommunication effectiveness in Ciboleger Community. Social distance both in Baduy Dalam and Baduy Luar effects one to another in term of effective communication between them. Social distance in Baduy Dalam effects their communication with Baduy Luar. The farther social distance in Baduy Dalam is, the less effective the communication is. Discrimination in Baduy Dalam community deeply determines the communication effectiveness with Baduy Luar.